2009
DOI: 10.1002/gea.20274
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential direct insolation as a degradation factor of cave paintings in Villar del Humo, Cuenca, Central Spain

Abstract: The purpose of this study is to assess the impact of direct sunlight on eleven given points of interest in Villar del Humo (Cuenca, Central Spain), and to determine to what extent this direct insolation, which is affected by both the regional and the local geomorphological configuration, influences the state and type of degradation of the paintings or of the host rock. The analysis of potential direct insolation with geographical information system (GIS) tools and morphometric field measurements shows that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In addition, the moisture conditions and the geological features are some of the local factors that can cause an increase in deterioration. 5,6 Furthermore, Díez-Herrero et al 7 have demonstrated that sunlight can have adverse effects on these types of paintings due to thermal and photochemical degradation. Thermal deterioration is caused by the nonuniform distribution of temperature between the rock's surface and the core, causing fissures or damage in the rock.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the moisture conditions and the geological features are some of the local factors that can cause an increase in deterioration. 5,6 Furthermore, Díez-Herrero et al 7 have demonstrated that sunlight can have adverse effects on these types of paintings due to thermal and photochemical degradation. Thermal deterioration is caused by the nonuniform distribution of temperature between the rock's surface and the core, causing fissures or damage in the rock.…”
Section: Introductionmentioning
confidence: 99%
“…haematite, limonite, clay minerals, and charcoal) are not very light sensitive. However, some authors have demonstrated that exposure to sunlight can have adverse effects on these systems due to thermal and photochemical degradation of the historic materials (Díez-Herrero et al, 2009). It has been determined that thermal deterioration is mostly observed in the host rock and is caused by the non-uniform distribution of temperature at the core of the material.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is planned to undertake some experiments (following Hall, 2004;Hall et al, 2005;Díez-Herrero et al, 2009) to study the impact of sunlight on exposed sandstone surfaces of different angles and aspects to better get an idea of the resulting changes in albedo and light-to-heat transfers. Finally, it is hoped to test a number of recent advances in chemical-based approaches to rock stabilization and surface protection (notably against graffiti; e.g., Fundazioa, 2009) in both the field and the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…A complication to all of this is the albedo of the rock and its components (see Hall, Guglielmin, & Strini, 2008b, for a discussion), as albedo is not constant but varies daily with the angle of the sun to the receiving surface (Oke, 1999) and changes through the year with the seasons. As Díez-Herrero et al (2009) have clearly demonstrated, solar insolation is a significant factor in causing the degradation of rock art, but its monitoring and evaluation are both complex and difficult.…”
Section: Introductionmentioning
confidence: 99%